The Reich Chancellery and Führerbunker complex : an illustrated history of the seat of the Nazi regime - Lehrer, Steven 1944- (McFarland, 2006)
"Germany's Nazi government made its primary headquarters in one of Berlin's oldest buildings: the Reich Chancellery. The site was frequented by Hitler and his inner circle. This complete history of the site focuses on the Nazi occupation" --Provided by publisher